The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/ijfs.13336
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of production process of ball mill refiner on some physical quality parameters of compound chocolate: response surface methodology approach

Abstract: Summary Chocolate compound was produced using ball mill refiner, and the effect of agitator shaft speed and refining time on the physical quality parameters (particle size, colour and steady‐state rheology) of compound chocolate was determined using response surface methodology. The shaft speed and refining time range were selected between 40–60 r.p.m. and 10–30 min, respectively. Determination coefficient of the models established for particle size, Newtonian viscosity and colour parameters (brightness, chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In previous studies, D 90 value measured by particle‐size distribution analysis was found to be very close to the value read by micrometer (Beckett, ; Toker et al, ). Therefore, the particle sizes of the produced chocolate samples and ingredients were determined by using micrometer (Mitutoyo, Manufacturing, Co., Ltd., Japan, 0.001 mm accuracy).…”
Section: Methodssupporting
confidence: 71%
“…In previous studies, D 90 value measured by particle‐size distribution analysis was found to be very close to the value read by micrometer (Beckett, ; Toker et al, ). Therefore, the particle sizes of the produced chocolate samples and ingredients were determined by using micrometer (Mitutoyo, Manufacturing, Co., Ltd., Japan, 0.001 mm accuracy).…”
Section: Methodssupporting
confidence: 71%
“…Superfine grinding technology, which crushes solid materials into powders less than 25 μm in diameter, has shown potential for production of nutraceuticals and functional foods (Chen, Weiss, & Shahidi, 2006;Wuhan, Erqi, & Ke, 2015). And ball milling treatment is a typical representative amongst the superfine grinding methods used in starches (Anzai, Hagiwara, Watanabe, Komiyama, & Suzuki, 2011;Dhital, Shrestha, & Gidley, 2010;Martinez-Bustos, Lopezsoto, San, Zazuetamorales, & Velezmedina, 2007;Tan et al, 2015), soybean protein isolate (Liu et al, 2017), chocolates (Alamprese, Datei, & Semeraro, 2007;Toker et al, 2017), mushroom powder (Wang et al, 2016), and wheat flours (Thanatuksorn, Kawai, Kajiwara, & Suzuki, 2009). As an eco-friendly and high-efficiency technology, ball milling changes the molecular arrangement of the surface of the food material, the individual particles for the human tongue to distinguish, and the crystal structure and the arrangement of electrons, resulting in several special effects, such as small size effect of protein particles, which are not available in the original food material.…”
Section: Introductionmentioning
confidence: 99%
“…For achieving an appropriate particle size, rening, conching and also ball mill process conditions such as rpm and time duration during chocolate processing play a key role. 31 Particle size of the treatments was in the acceptable range (<35 mm) reported for chocolate. 32 Polyols possess different numbers of hydrophilic active sites.…”
Section: Discussionmentioning
confidence: 78%
“…28 In a study by Gomes et al 36 it was shown that the particle size of chocolate samples (produced in a three-cylinder pilot mill and pilot conch) containing maltitol and lactitol ranged between 19 to 21 mm and it was in acceptable limit (<30 mm). Toker et al 31 investigated the effect of agitator sha speed (40-60 rpm) and rening time (10-30 min) of ball mill on some physical parameters of compound chocolate. The result illustrated that the particle size of the compound chocolates decreased significantly with increasing sha speed and rening time.…”
Section: Discussionmentioning
confidence: 99%